Maternal Factors Associated with Exclusive Breastfeeding Practices in Situbondo, Indonesia: A Cross-Sectional Study - Alivia Leyla Safira; Nurul Ulya Luthfiyana (KHD-Production, 2024)
Exclusive breastfeeding in the first six months significantly prevents morbidity and mortality. However, the coverage of exclusively breastfed 6-month-old infants in several sub-districts of Situbondo remains low. Understanding the determinants of breastfeeding practices is necessary to ensure successful breastfeeding promotion strategies. Therefore, this study aimed to assess the prevalence of exclusive breastfeeding and determine the maternal factors that relate to exclusive breastfeeding practices. This cross-sectional study involved 74 mothers with infants aged 6-9 months, selected using a systematic random sampling technique. Data was collected from May to August 2023 using validated questionnaires in Mangaran Sub-district, Situbondo, Indonesia. Chi-square or Fisher's Exact test was employed to identify the factors associated with exclusive breastfeeding. The exclusive breastfeeding proportion was 18.9%. The maternal factors significantly associated with exclusive breastfeeding included parity (OR= 4.79; 95% CI= 1.21 to 18.96, p-value= 0.018), breastfeeding self-efficacy (OR= 8.66; 95% CI= 1.06 to 70.66), and maternal autonomy (OR= 6.41; 95% CI= 1.32 to 31.14; p-value= 0.011). A large proportion of infants were not exclusively breastfed during the first six months. The results highlighted the significance of maternal factors in exclusive breastfeeding practices, particularly the aspect of breastfeeding empowerment. Women with a high breastfeeding self-efficacy and autonomy are more likely to practice exclusive breastfeeding, which by then suggests the need for comprehensive long-term programs. Interventions should be designed to strengthen empowerment in breastfeeding to improve breastfeeding outcomes.